La La doctrina del margen de apreciación nacional. Su recepción en el sistema europeo de Derechos Humanos en el Sistema Interamericano de Derechos Humanos y en Argentina - López Alfonsín, Marcelo Alberto (2016)
The national margin of appreciation is a hermeneutic rule born in the European system, which gives States a margin of deference to interpret conventional standards, taking the most direct contact national authorities have with civil society. The scope of this theory has transcended its primitive borders to be adopted by the inter-American system and Argentina, in particular. Contextual differences allow a comparison that shows the inter-American system in a rear most position relative to its European counterpart. In Argentina, this theory has been recognized, but has not reached a successful development.